2020
DOI: 10.4014/jmb.2004.04022
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Major Ginsenoside Rb1 to Rd by Dekkera anomala YAE-1 from Mongolian Fermented Milk (Airag)

Abstract: Dekkera anomala YAE-1 strain separated from "airag" (Mongolian fermented mare's milk) produces β-glucosidase, which can convert ginsenoside Rb 1 from Panax ginseng. Ginseng-derived bioactive components such as ginsenoside Rb 1 have various immunological and anticancer activities. Airag was collected from five different mare milk farms located near Ulaanbaatar, Mongolia. YAE-1 strains were isolated from airag to examine the hydrolytic activities of β-glucosidase on Korean Panax ginseng using an API ZYM kit. Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Additionally, the crude enzyme extract from Leuconostoc citreum can convert ginsenoside Rb1 in the following sequence: Rb1→Rd→F2→compound K [ 27 ]. Consistently, β-glucosidase isolated from D. anomala YAE-1 fully converted ginsenoside Rb1 to ginsenoside Rd after 48 h of incubation [ 14 ].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Additionally, the crude enzyme extract from Leuconostoc citreum can convert ginsenoside Rb1 in the following sequence: Rb1→Rd→F2→compound K [ 27 ]. Consistently, β-glucosidase isolated from D. anomala YAE-1 fully converted ginsenoside Rb1 to ginsenoside Rd after 48 h of incubation [ 14 ].…”
Section: Resultsmentioning
confidence: 91%
“…However, this strain did not metabolize ginsenoside Rb1 to ginsenosides Rb2 and Re. Finally, TLC analysis ( Figure 2 ) showed that LAB showing extracellular β-glucosidase activity only weakly metabolized ginsenoside Rb1 to ginsenoside Rd [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenoside Rd can be synthesized from ginsenoside Rb1 by the hydrolysis of glucose at C-20 ( Akter and Huq, 2018 ). The β-glucosidase produced by pectinase ( Fang et al, 2020 ), Dekkera anomala YAE-1 ( Renchinkhand et al, 2020 ), Paenibacillus sp. MBT213 ( Renchinkhand et al, 2017 ), Flavobacterium johnsoniae ( Hong et al, 2012 ), Leuconostoc mesenteroides DC102 ( Quan et al, 2011 ), and Lactobacillus brevis ( Zhong et al, 2016 ) is able to hydrolyze ginsenoside Rb1 (Rb1) and convert it to ginsenoside Rd during the fermentation of the ginseng.…”
Section: Biotransformation Of Ginsenoside Rdmentioning
confidence: 99%
“…β-glucosidase cleaves the glycoside at the C-3 position of ginsenoside Rd and produces the ginsenoside compound CK ( Renchinkhand et al, 2020 ). Ginsenoside M1 is formed by the hydrolysis of the C-3 glucose group in ginsenoside Rd by snailase ( Renchinkhand et al, 2017 ).…”
Section: Biotransformation Of Ginsenoside Rdmentioning
confidence: 99%